Effects of cascade damming on river hydrology, nutrient cycling and river biology: A review - Zheng, Yuran; Wang, Xun; Wang, Peifang; Yuan, Qiusheng; Xing, Xiaolei; Ren, Lingxiao; Liu, Sheng; Gan, Jiawen; Liu, Yunxin; Xia, Yufan (Science China. Technological sciences, 2025)
Rivers are dammed for purposes such as irrigation, flood control, water supply, navigation, and energy production. The cascade hydropower development of rivers has become an inevitable trend to meet the concurrent demands of economic growth and sustainable energy development and mitigate risks associated with global climate change. This development is unlikely to be halted in the near future. However, dams have profoundly altered river ecosystems, affecting hydrological conditions, material and energy transport, and biological structures. The presence of cascade dams and their potential cumulative effects have increased the complexity and severity of environmental impacts. In this paper, we present the response of eight research subjects—hydrological regime, water temperature, sediment, nutrient cycling, greenhouse gas emissions, fishes, benthic macroinvertebrates, and microorganisms—to cascade damming based on three broad directions of river hydrology, riverine nutrient cycling, and riverine organisms. We review the current status of research on the cumulative effects of cascade damming and explore the corresponding management measures and potential research directions. Finally, we summarize the challenges associated with studying these cumulative effects. This review aims to assist researchers in understanding the current status of cascade damming research and to stimulate discussions on achieving sustainable river development under the dual pressures of human needs and ecological protection.